Serum Alanine Aminotransferase Levels within Normal Range Have Different Associations with Augmentation Index and Other Cardiometabolic Risk Factors in Nondrinkers and Drinkers: A Chinese Community-Based Analysis - Shihui Fu; Chunling Liu; Leiming Luo; Ping Ye (Gastroenterology Research and Practice)
Background. To investigate whether serum alanine aminotransferase (ALT) levels within normal range were associated with augmentation index (AIx) and cardiometabolic risk factors in nondrinkers and drinkers in Chinese community-dwelling population. Methods. There were 4165 participants with serum ALT levels within normal range. Results. Alcohol drinking was observed in 1173 participants (28.2%). In multivariate analysis, serum ALT levels of nondrinkers were independently associated with age, sex, body mass index (BMI), hypertension, diabetes mellitus, diastolic blood pressure, triglyceride, low-density lipoprotein-cholesterol (LDL-c), and AIx, while serum ALT levels of drinkers were independently associated with age, sex, BMI, triglyceride, and LDL-c (p<0.05 for all). Conclusions. Associations of serum ALT levels within normal range with age, sex, body height and weight, and blood lipid were simultaneously present in participants with and without alcohol drinking, while associations of serum ALT levels within normal range with AIx, blood pressure, and glucose were seen in nondrinkers rather than in drinkers. These findings not only provide the evidence that serum ALT levels, even within the normal range, have different associations with arteriosclerosis and cardiometabolic risk factors in nondrinkers and drinkers but also are helpful in understanding the underlying pathophysiologic mechanisms linking the hepatic function to arteriosclerosis and cardiometabolic risk factors.